Biologics in Psoriasis: Updated Perspectives on Long-Term Safety and Risk Management [Corrigendum] - Al-Janabi A; Yiu ZZN (Dove Medical Press, 2022)
Al-Janabi A, Yiu ZZN. Psoriasis (Auckl). 2022;12:1–14. The authors have advised that there is an error in Table 1 on page 2. The text “IL-7A” in the Target column for the Ixekizumab row should read “IL-17A”. The authors apologize for this error. Read the original article